Production of Oyster Mushrooms in Different Seasonal Conditions of Bangladesh - Uddin, M. N.; Yesmin, S.; Khan, M. A.; Tania, M.; Moonmoon, M.; Ahmed, S. (Journal of Scientific Research, 2010)
Oyster mushrooms (Pleurotus spp.) are widely cultivated all over the world. Its production is remarkably affected by the environmental conditions like temperature and relative humidity. In this study, we investigated the production of four species of oyster mushroom: Pleurotus ostreatus, P. florida, P. sajor-caju and P. high king cultivated in every season (January to December) in Bangladesh. The temperature (in 0C) and relative humidity (% RH) of culture house in each month, and parameters of mushroom production were recorded. In all of the selected species of this study, the minimum days required for primordial initiation, and the maximum number of fruiting bodies, biological yield and biological efficiency were found in December to February (14-27 0C, 70-80% RH). The production was found minimum during the cultivated time August to October. We suggest cultivation of selected Pleurotus spp in winter (temperature zone 14-27 0C with relative humidity 70-80%) for better production and biological efficiency. Keywords: Pleurotus mushroom; Different seasonal conditions; Growth and yield; Biological efficiency. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i1.6130 J. Sci. Res. 3 (1), 161-167 (2011)